1997
DOI: 10.1002/(sici)1097-0320(19970401)27:4<365::aid-cyto8>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces S-phase apoptosis in cis-diamminedichloroplatinum-treated cells, whereas cis-diamminedichloroplatinum induces a block in G2/M

Abstract: Caffeine overrides checkpoints in the G2 phase of the cell cycle by inhibiting DNA repair at this phase and increases the cytotoxicity of antitumor drugs, such as cis‐diamminedichloroplatinum (CDDP). The enhanced cell death induced by caffeine is characterized by apoptosis. In this paper, we demonstrate that this apoptotic event occurs in S phase of the cell cycle, whereas CDDP induces a block in G2/M. DNA histogram analysis revealed that caffeine reduced G2 arrest in CDDP‐treated EL‐4 cells. In a synchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Furthermore, in previous studies we investigated the apoptosis rates 72 and 96 hr after irradiation and observed a rather slow and delayed induction of apoptosis in both cell lines, which was not correlated to clonogenic survival [20,31]. A correlation between the abrogation of G2/M arrest and apoptosis was mostly found, but not in in all cases [32][33][34][35][36][37][38][39]. In accordance with our study, caffeine-mediated sensitization may not always correlate with an enhancement of apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in previous studies we investigated the apoptosis rates 72 and 96 hr after irradiation and observed a rather slow and delayed induction of apoptosis in both cell lines, which was not correlated to clonogenic survival [20,31]. A correlation between the abrogation of G2/M arrest and apoptosis was mostly found, but not in in all cases [32][33][34][35][36][37][38][39]. In accordance with our study, caffeine-mediated sensitization may not always correlate with an enhancement of apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…6D), consistent with previous reports on the induction of apoptosis by caffeine. [35][36][37] To test whether caffeine-induced apoptosis is dependent on autophagy, we determined whether the inhibition of autophagy by 3-methyladenine (3-MA) or Atg7 siRNA knockdown affects caffeine-induced cytotoxicity in PC12D cells. Treatment with 1 or 5 mM 3MA or Atg7 knockdown significantly decreased the percentage of cell death or cells with reduced mitochondrial membrane potentials caused by caffeine treatment (5 or 10 mM) (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…It is known that drug sensitivity to anticancer agents is highest in the G2‐M phase of the cell cycle 28–30 . Suspecting that combination chemotherapy of nobiletin with an anticancer agent would be more effective than treatment with a conventional cytotoxic drug alone, we evaluated the combination effect of nobiletin with cisplatin (CDDP) by MTT assay in TMK‐1 and MKN‐45 cells.…”
Section: Combined Effect Of Nobiletin With An Anticancer Drug Cddp mentioning
confidence: 99%